Procedures for Conducting Ethnographic Research and Research Case Studies - Watsuji, Taketo; Hohashi, Naohiro; Lin, Qiting; Ota, Hiroko (Journal of Japan Society of Nursing Research, 2022)
Ethnographic research is "a methodology for describing phenomena and cultures occurring in the living world of subjects from emic and etic perspectives, performed through fieldwork that consists primarily of ethnographic interviews and participant observation." This is conducted through a triangulation of methods: formal and informal interviews, participant observation, questionnaire surveys, collection of existing books, literatures, website materials, photography and video recording. Questions and hypotheses are refined through repeated data collection and analysis. Trustworthiness is ensured by criteria to evaluate qualitative research studies, including credibility, confirmability, meaning-in-context, recurrent patterning, saturation, transferability. All data are qualitatively described in fieldnotes, encoded, categorized in terms of similarities and differences in codes, after which it is summarized in a narrative report on stories in accordance with a theme.